Development of Demonstration-Assisted Audio Visual Media to Improve Students' Critical Thinking - Fajar Agus Hari Firmansyah; Waspodo Tjipto Subroto; Hendratno Hendratno (IKIP Mataram, 2023)
Based on the needs analysis that was carried out in Class V SD Al-Islam Gresik, there is an obstacle that teachers have limitations in teaching, one of which is influenced by the availability of educational media that can help teachers use simple media that are located around the classroom area and have never used media. audio visual in the form of 3D in education. Based on data analysis and discussion of research results, then associated with the formulation of the problem and research objectives, the conclusion was obtained, namely media validation from the results of media experts with very good grades. The validator gives a score of 96%, meaning that audio-visual media with validation from experts is very feasible to use, material validation from the results of material experts with very good grades. The validator gives an assessment reaching 93%, meaning that audio-visual media with validation from experts is very feasible to use, the practicality of the media gets grades from the teacher in a very practical category, the teacher gives an assessment that reaches 95%, meaning that the media developed is feasible to use and very practical on a small scale because it does not require a lot of time, the practicality of the media gets value from student responses in the very practical category, students give an assessment with a 90% percentage mode, meaning that the developed media is feasible to use and is very practical on a small scale (n = 5 children) because it does not require much time. a lot, the effectiveness of the media gets a score from student responses in the very effective category, students give an assessment with a 90% percentage mode meaning that the media developed is feasible to use and very effective on a large scale (n = 10 children) because the efficiency of critical thinking in students has increased.